Object and consciousness in dialectical materialism. A contribution to the theory of social communication - Andrzejewski, Bolesław (Lingua Posnaniensis, 2017)
The aim of the paper is to describe one of the theories of man, then of those regarding language and communication. There are many concepts related to these categories. Most of them define man as an independent being from outside, significant external influences. Dialectical materialism goes a different way in which man is a part of material world. Moreover, our language and communication have their roots and exist in the objective environment.